Clinical Reasoning: A 48-Year-Old Woman Presenting With Vertigo, Ptosis, and Red Eyes. (19th April 2022) - Kim, Keun-Tae; Baek, Seol-Hee; Lee, Sun-Uk; Kim, Jung Bin; Kim, Ji-Soo
Abstract : We describe acute vestibular syndrome in a 48-year-old woman with breast cancer who was finally found to have anti–Ma2-associated encephalitis. Although the initial diagnosis was vestibular neuritis elsewhere, progression of symptoms and additional findings of bilateral ptosis and circumlimbal injections, vertical saccadic slowing, and impaired convergence led to a suspicion of a rostral midbrain lesion and final diagnosis. The patient's symptoms and ocular motor signs improved markedly after administration of IV methylprednisolone and oral tacrolimus. Our patient again stresses the importance of scrutinized ocular motor evaluation for detection of central lesions even in patients with the clinical features of unilateral peripheral vestibulopathy.